Tissue preparation for simultaneous flow cytometric quantitation of tumour associated antigens and DNA in solid tumours. Issue 10 (October 1990) - van Dam, P A; Watson, J V; Lowe, D G; Cox, H; Curling, M; Shepherd, J H
Abstract : A multiparameter flow cytometric assay for the simultaneous study of tumour associated antigens (TAA) and DNA in fresh solid tumours was devised. Cell suspensions were prepared by disaggregating unfixed solid tumour samples mechanically over a stainless steel mesh. Indirect immunofluorescence was used to identify the TAA, and DNA was stained with propidium iodide. Cell morphology was well preserved, cell clumping was negligible, and high quality indirect immunofluorescence quality indirect immunofluorescence and DNA staining were obtained. The technique is simple, rapid, and reproducible. Multiparameter assays can be developed to study prognostic indicators such as membrane oncoproteins, receptors, and multidrug resistance in solid tumours. With a suitable panel of antibodies the technique might become an aid in the differential diagnosis and biochemical diagnosis of some solid tumours.